ADAM SMITH AND THE ORIGINS OF POLITICAL ECONOMY. Issue 1 (2020) - Paganelli, Maria Pia
Abstract: The method of analysis Adam Smith uses is relatively similar to the method economics generally uses today, especially the subfield of experimental economics. The method of analysis that Smith uses is coherent and consistent throughout his whole work. He searches for constant variables and then sees what variables are changed by exogenous changes. In particular, Smith looks for the constancy in human nature, and analyzes how historical and material circumstances change the incentives that the constant human nature faces. This method, applied to human conduct in all its aspects, makes it easy for many economists today to see some continuity between Smith's political economy and today's economic science.